Implementation of a comprehensive program to improve coordination of care in an urban academic health care system. Issue 5 (10th August 2018) - Hsiao, Ya Luan; Bass, Eric B.; Wu, Albert W.; Richardson, Melissa B.; Deutschendorf, Amy; Brotman, Daniel J.; Bellantoni, Michele; Howell, Eric E.; Everett, Anita; Hickman, Debra; Purnell, Leon; Zollinger, Raymond; et al.
Abstract : Purpose: Academic healthcare systems face great challenges in coordinating services across a continuum of care that spans hospital, community providers, home and chronic care facilities. The Johns Hopkins Community Health Partnership (J-CHiP) was created to improve coordination of acute, sub-acute and ambulatory care for patients, and improve the health of high-risk patients in surrounding neighborhoods. The paper aims to discuss this issue. Design/methodology/approach: J-CHiP targeted adults admitted to the Johns Hopkins Hospital and Johns Hopkins Bayview Medical Center, patients discharged to participating skilled nursing facilities (SNFs), and high-risk Medicare and Medicaid patients receiving primary care in eight nearby outpatient sites. The primary drivers of the program were redesigned acute care delivery, seamless transitions of care and deployment of community care teams. Findings: Acute care interventions included risk screening, multidisciplinary care planning, pharmacist-driven medication management, patient/family education, communication with next provider and care coordination protocols for common conditions. Transition interventions included post-discharge health plans, hand-offs and follow-up with primary care providers, Transition Guides, a patient access line and collaboration with SNFs. Community interventions involved forming multidisciplinary care coordination teams, integrated behavioral care and new partnerships with community-based organizations. Originality/value: This paper offers a detailed description of the design and implementation of a complex program to improve care coordination for high-risk patients in an urban setting. The case studies feature findings from each intervention that promoted patient engagement, strengthened collaboration with community-based organizations and improved coordination of care.